Analysis of the composition and processing technologies of dispersed iron‑containing waste - N. I. Urbanovich; S. V. Korneev; V. I. Volosatikov; D. O. Komarov (Литьë и металлургия, 2021)
The article discusses the types of various dusty iron‑containing waste generated in metallurgical and foundry production. Rational waste processing technologies are considered. The analysis of the chemical composition of iron‑containing waste, morphology and particle size is presented. Variants of processing and use technology that are acceptable for the conditions of the Republic of Belarus are proposed.